Generation and enhancement of SRS sub-nanosecond pulses in self-focusing organic substances - Isaenko, O.Iu.; Ivanisik, A.I.; Korotkov, P.A.; Ponezha, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The possibility to use self-focusing organic substances in order to create
highly efficient transformers of laser radiation based on stimulated Raman scattering has
been researched. The proposed and implemented optical schemes are suitable for
generation of seed sub-nanosecond Stokes pulses, due to dynamics of self-focusing, and
the compression of giant pulses of multimode laser with high (>20) increase in the
intensity at a shifted frequency